A comprehensive review on the antiviral activities of chalcones. (21st April 2021) - Elkhalifa, Dana; Al-Hashimi, Israa; Al Moustafa, Ala-Eddin; Khalil, Ashraf
Abstract: Some viral outbreaks have plagued the world since antiquity, including the most recent COVID-19 pandemic. The continuous spread and emergence of new viral diseases have urged the discovery of novel treatment options that can overcome the limitations of currently marketed antiviral drugs. Chalcones are natural open chain flavonoids that are found in various plants and can be synthesised in labs. Several studies have shown that these small organic molecules exert a number of pharmacological activities, including antiviral, anti-inflammatory, antimicrobial and anticancer. The purpose of this review is to provide a summary of the antiviral activities of chalcones and their derivatives on a set of human viral infections and their potential for targeting the most recent COVID-19 disease. Accordingly, we herein review chalcones activities on the following human viruses: Middle East respiratory syndrome coronavirus, severe acute respiratory syndrome coronavirus, human immunodeficiency, influenza, human rhinovirus, herpes simplex, dengue, human cytomegalovirus, hepatitis B and C, Rift Valley fever and Venezuelan equine encephalitis. We hope that this review will pave the way for the design and development of potentially potent and broad-spectrum chalcone based antiviral drugs.